Elongation and maturation of c-myc RNA is inhibited by differentiation inducing agents in HL60 cells. - Eick, D (1990)
Maturation of c-myc mRNA proceeds in a given order in HL60 cells. It starts with splicing of intron 2, continues with splicing of intron 1 and ends with 3' cleavage and polyadenylation of the primary transcript. This process is inhibited, when HL60 cells were induced to terminal differentiation by dimethylsulfoxide (DMSO). DMSO interferes specifically with maturation of c-myc but not c-abl RNA in HL60 cells. Simultaneously, DMSO induces a block to RNA elongation at the boundary of c-myc exon 1 and intron 1 in HL60 cells. Participation of the same factor(s) in the regulation of c-myc RNA elongation and splicing is supposed.